2007
DOI: 10.1111/j.1471-4159.2007.04525.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical, morphological, and neurophysiological abnormalities in retinas of Sandhoff and GM1 gangliosidosis mice

Abstract: Retinal abnormalities are well documented in patients with ganglioside storage diseases. The total content and distribution of retinal glycosphingolipids was studied for the first time in control mice and in Sandhoff disease (SD) and GM1 gangliosidosis mice. Light and electron microscopy of the SD and the GM1 retinas revealed storage in ganglion cells. Similar to previous findings in rat retina, GD3 was the major ganglioside in mouse retina, while GM2 and GM1 were minor species. Total ganglioside content was 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…4C) indicative of increased "anxiety-like" behavior in the hexb−/−mice. We have employed a behavioral test battery to assess a mouse model of Sandhoff disease that we backbred onto the C57BL/6J background.We demonstrated deficits in motor activity, and coordination consistent with those previously reported [1,7,8,13,14,16,18,20,22,25,27,28] suggesting no significant effect of genetic background. However, we were also able to detect deficits as early as 66 days using the balance beam test.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…4C) indicative of increased "anxiety-like" behavior in the hexb−/−mice. We have employed a behavioral test battery to assess a mouse model of Sandhoff disease that we backbred onto the C57BL/6J background.We demonstrated deficits in motor activity, and coordination consistent with those previously reported [1,7,8,13,14,16,18,20,22,25,27,28] suggesting no significant effect of genetic background. However, we were also able to detect deficits as early as 66 days using the balance beam test.…”
supporting
confidence: 91%
“…Previous electrophysiological studies of visual function in Sandhoff mice have been reported in older mice (3.5-4 months). Electroretinograms were normal even at this late stage while visual evoked potentials were generally present [7]. These data, in combination with the normal levels of novel object exploration in Trial 1, normal pupil dilation and normal visual placing in the FOB suggest that deficits in visual function are not sufficient to explain the poor performance in the memory tests.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Indeed, GG composition of the retina undergoes drastic changes during the development of the tissue, concomitantly to morphologic differentiation ( 15 ). Mouse models of GM2 gangliosidosis exhibit retinal abnormalities with visual defi ciency ( 16,17 ). Moreover, GM1 injections into the vitreous can protect the retina from lesions induced by ischemia ( 18 ) or optic nerve axotomy ( 19 ).…”
Section: Extraction Separation and Purifi Cation Of Ggsmentioning
confidence: 99%